Origins, history and social structure in Brunei Darussalam
1 online resource (xxix, 198 pages
Keywords: This wide-ranging book re-evaluates in detail the early history and historiography of Brunei Darussalam, the origins of the sultanate, its genealogical foundations and the structure and administration of Brunei society. Contributors draw on the seminal work of Donald E. Brown whose major monograph on the sultanate was published in 1970 and marked the beginnings of advanced sociological, anthropological and historical research on Brunei. Among the key issues addressed are status systems, titles and social stratification, Chinese sources for the study of Brunei, Malay oral and written histories and traditions, the symbolism, meanings and origins of coronation rituals, previously unknown sources for the study of Brunei history and the processes of incorporation of minority populations into the sultanate. Contributions by leading scholars of Brunei, Borneo and the wider Indonesian-Malay world, both from within Brunei Darussalam and beyond, address some central preoccupations which Brown raised and which have been the subject of continued debate in Austronesian and Southeast Asian studies. A novel contribution to the study of the history of Brunei Darussalam, this book will be of interest to scholars of Southeast Asian history, Asian history, Colonial and Imperial history and anthropology.